Remote Vehicle Monitoring System Starting and Tracking Using IoT System - Abd Rahman, Mohamad Izzul Sham; Sulaiman, Syabillah; Azizul, Muhamad Asri (Journal of Automotive Powertrain and Transportation Technology, 2023)
Safety in the vehicle is one of the most important factors in the daily life of every vehicle user. This project is more focused on improving vehicle systems to increase vehicle safety systems. The main objective of this project is to study IoT (Internet of Things) safety systems in automotive applications. Next is to design engine start-stop and tracking for motorcycles. In addition, to analyze battery voltage, GPS location data, and engine start-stop system from the motorcycles with safety features. The vehicle used for this project is a Yamaha 135LC version 2 motorcycle, the Blynk app, and a two NodeMCU ESP8266 microcontroller with a Wi-Fi module, a relay, and a GPS module. As a result of the start-stop engine, PicoScope was used to analyze the voltage of the battery after the system had fully functioned when the signal was sent to the relay by Blynk apps. The experiment was carried out from five different locations for the engine start-stop system and seven different locations for the GPS, with the engine start-stop system obtaining motor battery voltage readings using PicoScope and the GPS obtaining vehicle coordinate results by reading the latitude and longitude from the smartphone. The GPS data was then compared between the location of the GPS module and the location of the smartphone's GPS to determine the accuracy of the location.